A FANTASY COMING TO LIFE AND THE POSTCOLONIAL SHAME – POLISH MIGRATION NARRATION IN THE BRITISH ISLES. - Jaremek, Magdalena (Porównania, 2019)
Magdalena Jaremek, A FANTASY COMING TO LIFE AND THE POSTCOLONIAL SHAME – POLISH MIGRATION NARRATION IN THE BRITISH ISLES. “PORÓWNANIA” 1 (24), 2019. Vol. XXIV, P. 163-174. ISSN 1733-165X. The article concerns Polish contemporary migration narratives in the British Isles after Poland’s accession to the European Union. The author analyses selected novels and short stories through the prism of psychoanalysis and postcolonial theory, utilizing the concept of ‘surrogate hegemon’ proposed by Ewa M. Thompson. From the partitions in the late 1700s until the demise of communism in 1989, the conquered Polish population repeatedly experienced shame and humiliation. These experiences left an indelible mark on the minds of numerous Poles who drifted off into the fantasy of the idealized West. Social changes, such as globalization and open borders, fostered the translocation of a large number of predominantly young and middle-aged Poles to the British Isles. Thus, the fantasy has come true, yet bringing about unexpected results: Polish postcolonial subject, having reached the dream location, was eventually given opportunity to confront their utopian expectations with harsh reality. The author seeks an answer to the question how postcolonial resentment, founded on the victim’s memory and further intensified by present experiences of embarrassment and intimidation in the migrant destination society, influences the subject’s identity.